Danielle M. Wenner Replies - Wenner, Danielle M. (The Hastings Center report, 2019)
The author replies to a letter to the editor from Felicitas Sofia Holzer concerning Wenner’s article “The Social Value Requirement in Research: From the Transactional to the Basic Structure Model of Stakeholder Obligations,” in the Hastings Center Report’s January-February 2019 issue.